Perbaikan Stasiun Kerja Guna Meningkatkan Efisiensi Gerakan dan Produktivitas pada Operator Divisi Manual Oplos PT.XYZ - Arga Juniv Samsudin; Handy Febri Satoto (Fakultas Teknik UMRI, 2024)
PT. XYZ a manufacturing company focused on the production of paper, notebooks, and chemicals, faces challenges in the inefficient manual mixing process. This process involves a lot of wasteful movements and unergonomic workplace arrangements, resulting in operator discomfort, long cycle times, and low productivity. This study aims to evaluate and improve the manual mixing work system in the manual insert department, by highlighting the problems of inefficient movements and improving work safety and comfort. Improvements were made through the application of ergonomic principles, including rearranging the layout and adding a feeder role (tools used to provide raw materials or materials to the work area). The results showed that with the implementation of these improvements, the average cycle time was significantly reduced from 639 seconds per rim to 132 seconds per rim, or a reduction of 79.34%. In addition, production output increased rapidly from 42 rims to 204 rims in 7.5 working hours, increasing production efficiency by 385.71%. Not only that, irregular job time was also drastically reduced, increasing operational efficiency from 57% to 99%. These improvements have successfully reduced operator physical fatigue, increased productivity, and created a more ergonomic and comfortable working environment. These results demonstrate the importance of ergonomic approaches and work system optimization in improving company performance.